Deadly biocultures : the ethics of life-making - Ehlers, Nadine; Krupar, Shiloh R. (University of Minnesota Press, 2019)
"This book project intends to serve as a course adoption book unpacking theories of biopolitical life-making and death-making, with chapters dedicated to specific objects that ostensibly affirm life (and argue for life's inextricable links to capital), but that ultimately reify a politics of death and erasure. Specific objects, such as the pink Kommen Foundation-branded handgun, the 'super user' of health care resources, and fat cells allow the authors to discuss the political junctures at which determinations of healthy and unhealthy, life and death, are made"--